2018
DOI: 10.1088/1748-0221/13/01/p01013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a compact D-D neutron generator

Abstract: A: A compact D-D neutron generator was developed at Lanzhou University, China. A duoplasmatron ion source was used to produce a higher-current deuteron beam. The deuteron beam could be accelerated up to 150 keV by a single accelerating gap, and bombarded on a pure molybdenum drive-in target to produce D-D fast neutron. A bias voltage between the target and the extraction-accelerating electrode was produced by a resistance to suppress the secondary electron from the target. The neutron generator has been operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Therefore, it is also observed that −J ex decreases as t Ir increases. To quantitatively measure −J ex , the TR-MOKE technique was employed to study the p-SAFs [73] up to the THz range, TR-MOKE is a powerful tool to characterize p-SAFs with high PMA and IEC. By fitting the fielddependent f in the high-(HF) and low-frequency (LF) modes, J ex (defined as J ex = J 1 + 2J 2 ) can be extracted, with J 1 and J 2 the bilinear and biquadratic exchange coupling constants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is also observed that −J ex decreases as t Ir increases. To quantitatively measure −J ex , the TR-MOKE technique was employed to study the p-SAFs [73] up to the THz range, TR-MOKE is a powerful tool to characterize p-SAFs with high PMA and IEC. By fitting the fielddependent f in the high-(HF) and low-frequency (LF) modes, J ex (defined as J ex = J 1 + 2J 2 ) can be extracted, with J 1 and J 2 the bilinear and biquadratic exchange coupling constants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…By fitting the fielddependent f in the high-(HF) and low-frequency (LF) modes, J ex (defined as J ex = J 1 + 2J 2 ) can be extracted, with J 1 and J 2 the bilinear and biquadratic exchange coupling constants, respectively. [73][74][75] As a representative example, Figure 6c shows the field-dependence of f in both precessional modes of Sample 1. The fitting curve gives −J ex = 3.48 ± 1.09 mJ m −2 , which is ≈34% larger compared to the former result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Designing deuteron accelerators facilities such as IFMIF/EVEDA [1] and BISOL [2], and FNG [3], where the deuteron beam interacts with a deuterated/tritiated target to produce neutrons, requires a computational approach which simulates the D-T fusion interaction with acceptable accuracy. This approach can also help to improve the design of the compact neutron generators for different applications [4]. In principle, the approach for simulating the D-T fusion interaction should be able to simulate the deuteron transport in the target, in order to describe details of the deuteron interactions, to produce secondary particles, and finally, to simulate the transport of secondary particles in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Compact neutron generators are considered in this work as sources based on accelerated ion beams extracted from plasma.. As an example, one can consider the following sources: Adelphi [18], Efremov NIIEFA [19], LBNL [20], Lanzhou University [21]. The typical beam energy is 100−300 keV at a current of a few−tens mA.…”
Section: Introductionmentioning
confidence: 99%